Analyisis Of The Effect Of Using Spice Boiled Water On The Quality Of Donuts - Syaqhila, Putri; Yelfi, Reno; Elida, Elida; Anggraini, Ezi (Universitas Negeri Padang, 2024)
This research is motivated by innovation in the use of spices in liquid form which are used as liquid ingredients in making donuts. The aim of this research is to analyze the effect of using 10gr 3gr 3gr, 13gr 6gr 6gr, 15gr 9gr 9gr,15gr 10gr 10gr spices (cinnamon, anise, cloves) on the quality of donuts in terms of aroma and taste. This type of research is an experiment with a completely randomized design (CRD) method and one repetition. The data source in this research was obtained from 3 expert panelists, namely lecturers at the Department of Family Welfare Science, Culinary Education Concentration, Faculty of Tourism and Hospitality, Padang State University. The tool used to collect data was a questionnaire containing questions about the quality of the donuts. Data were analyzed using ANOVA, if Fcount ≥ Ftable then continued with the Duncan test. The results of the research showed that there was a significant effect of using boiled spice water between 10gr cinnamon, 3gr anise, 3gr cloves (X1), 13gr cinnamon, 6gr anise, 6gr cloves (X2), 15gr cinnamon, 9gr anise, 9gr cloves (X3), 15gr cinnamon, 10gr anise, 10g cloves (X4) on the quality of the donuts, namely the quality of the aroma typical spices and typical spice taste. The best quality test results for spiced donuts were in treatment X4 with the use of spices of 15g cinnamon, 10g anise and 10g cloves..